Origins of the war in the East Britain, China and Japan 1937-39 - Shai, Aron (Routledge library editions. Japan, 2013)
This study describes the British government's policy towards China during the first phases of the undeclared Sino-Japanese war, starting in July 1937 when the conflict in North China culminated in all-out hostilities; and ending in September 1939 when the outbreak of the war over Poland forced the British government to turn almost all its attention to Europe. The dilemmas confronting British policy-makers in the Far East are analysed together with the implementation of their subsequent solutions. Attention is focused on the question of British interests in China and on the decisive factors and considerations which determined British policy and Britain's role in the Sino-Japanese war. Questions concerning the safety of the British subjects and the commercial community in China and their influence on the decision making process, the attitude towards Soviet influence in China and prospects of Communist take-over are also discussed. In the final analysis the book examines the widely debated subject of appeasement in its Asian context. It is argued that Britain pursued a policy towards Japan which gained strength without producing a Far Eastern Munich